The Effect of Burnable Poison Np-237 on the Conceptual Design of the GFR-2400 MWt Using MCANDLE Burnup Strategy - Monado, Fiber; Berliani, Berliani; Supardi, Supardi; Royani, Idha; Ariani, Menik; Kaban, Hadir; Su'ud, Zaki (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2024)
This study was used to design the Gas-cooled Fast Reactor (GFR) with 2400 MWt power as well as to implement a modified CANDLE (MCANDLE) burning strategy. Metallic uranium with Neptunium-237 at a concentration of 1% to 10% was used as burnable poison in the fuel while helium was applied as a coolant. Neptunium has been produced in conventional reactors by the decay product of plutonium obtained from U-238. This isotope has a relatively high absorption cross-section. As a nuclear waste, it is very useful to utilize as a burnable poison to reduce waste in the future and extend reactor operation lifetime with negligible reactivity. Moreover, the reactor was designed to operate for 100 years of burnup. Nuclear Fuel cell level calculations were conducted using the PIJ module and the reactor core was analyzed using the CITATION module contained in the SRAC. The core height was found to be 420 cm while the diameter was 300 cm and it was designed to have a refueling period of ten years. The survey parameters evaluated include burnup level, factor multiplication, conversion ratio, atomic density, and power distribution. The calculation conducted at the fuel cell level showed that the maximum value in the 76th year for the infinite multiplication factor was 1.30097. It was also discovered that the reactor core for the effective multiplication factor parameter with a fuel fraction of 55% was 1.094 without the addition of burnable poison.